Improving Profitability Using Predictive Analytics - Roy, Bhaskar; Bera, Debabrata; Tripathi, Praveen Kumar; Upadhyay, S. K. (Indian Journal of Marketing, 2021)
The objective of this paper was to explore a better pricing strategy by predicting contribution margin (CM) to drive wins at higher prices. This paper focused on the services industry, where macroeconomic factors play a key decisive role in arriving at contribution margin to win more deals in this competitive market. The paper incorporated prior research findings to develop a multidimensional and multifaceted framework depicting the methodology of formulating customer value for value-based pricing. The empirical portion of this paper contained a case study based on masked industry data from an industrial manufacturing company dealing with products and services. We discussed and highlighted the criticality of identifying and capturing the right features while creating the right pricing strategy using multiple linear regression and decision tree techniques. Applying the predictive analytics approach helped us estimate the contribution margin with a higher winning probability during contract negotiation. This paper would aid organizations to develop and implement an enterprise-wide strategic pricing discipline designed to bolster the value and impact of their products and service pricing.